Mycetoma Medical Therapy - Welsh, Oliverio; Al-Abdely, Hail Mater; Salinas-Carmona, Mario Cesar; Fahal, Ahmed Hassan (PLOS Neglected Tropical Diseases, 2014)
Medical treatment of mycetoma depends on its fungal or bacterial etiology. Clinically, these entities share similar features that can confuse diagnosis, causing a lack of therapeutic response due to inappropriate treatment. This review evaluates the response to available antimicrobial agents in actinomycetoma and the current status of antifungal drugs for treatment of eumycetoma.